2010
DOI: 10.5194/acp-10-11737-2010
|View full text |Cite
|
Sign up to set email alerts
|

Reconciliation of measurements of hygroscopic growth and critical supersaturation of aerosol particles in central Germany

Abstract: Abstract. Aerosol physical, chemical and hygroscopic properties were measured in a range of airmasses during COPS (Convective and Orographically-induced Precipitation Study) ground-based in June and July of 2007 at the Hornisgrinde mountain site in the Black Forest, Southwest Germany. Non-refractory aerosol composition was measured with an Aerosol Mass Spectrometer, simultaneous to hygroscopic growth factors at 86% relative humidity and CCN activity measurements for particles of dry (< 20%) diameters 27 to 217… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 49 publications
5
89
0
Order By: Relevance
“…Measurements of the hygroscopic growth of atmospheric aerosols in both subsaturated and supersaturated conditions have demonstrated discontinuities in water-uptake behavior below and above water saturation Irwin et al, 2010Irwin et al, , 2011Dusek et al, 2011;Ovadnevaite et al, 2011;Hersey et al, 2013). Specifically, for a given population of aerosols, previous studies have observed low degrees of hygroscopic growth below water saturation but high CCN activity.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the hygroscopic growth of atmospheric aerosols in both subsaturated and supersaturated conditions have demonstrated discontinuities in water-uptake behavior below and above water saturation Irwin et al, 2010Irwin et al, , 2011Dusek et al, 2011;Ovadnevaite et al, 2011;Hersey et al, 2013). Specifically, for a given population of aerosols, previous studies have observed low degrees of hygroscopic growth below water saturation but high CCN activity.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, however, have either implicitly or explicitly reported significant discrepancies between κ chem and κ app (e.g. Moore et al, 2008;Engelhart et al, 2008;King et al, 2009;Wex et al, 2009;Good et al, 2010a;Irwin et al, 2010;Padro et al, 2010). This discrepancy has been attributed to a combination of several effects, including gradual dissolution of sparingly soluble compounds at high relative humidity Petters et al, 2009b), highly non-ideal solution behaviour (Prenni et al, 2007;Petters et al, 2009b), measurement uncertainties related to HTDMA operation including residence time and other unresolved sources of disagreements between instruments of similar design (Sjogren et al, 2007;Good et al, 2010b), and unaccounted surface tension effects when applying Eq.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy has been attributed to a combination of several effects, including gradual dissolution of sparingly soluble compounds at high relative humidity Petters et al, 2009b), highly non-ideal solution behaviour (Prenni et al, 2007;Petters et al, 2009b), measurement uncertainties related to HTDMA operation including residence time and other unresolved sources of disagreements between instruments of similar design (Sjogren et al, 2007;Good et al, 2010b), and unaccounted surface tension effects when applying Eq. (1) to derive κ app (Moore et al, 2008;Engelhart et al, 2008;King et al, 2009;Wex et al, 2009;Good et al, 2010a;Irwin et al, 2010;Padro et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Such a protocol should minimise sampling artefacts of condensation and evaporation. Discrepancies between online measurements of composition and hygroscopic growth when particles contain substantial amounts of semi-volatile material show that correction for this fraction are required , and the equilibration of semi-volatile material will likely contribute to discrepancies between measurements of chemical composition, sub-saturated hygroscopic growth and droplet activation in the laboratory (Good et al, 2010c) and atmosphere (Irwin et al, 2010).…”
Section: Precursormentioning
confidence: 99%